Quantum‐chemical‐aided design of copolymers with tailored bandgaps and effective masses: The role of composition (2010)
Extending a key observation made by Meyers et al. (Meyers et al., J Chem Phys, 1992, 97, 2750), a strategy for the systematic design of conducting polymers with tailor‐made bandgaps and carrier effective masses is described and quantum‐chemically implemented. Such strategy relies on the construction of alternating binary copolymers from well‐characterized parent polymers, in such a manner that those electronic parameters can be phenomenologically predicted from the composition of the copolymer. Illustrative calculations for three types of alternating copolymers built from five parent π‐conjugated polymers demonstrate the plausibility of the methodology and the internal consistency of its computational implementation. Specifically, it is shown that the bandgaps of copolymers built from parent monomers with similar chemical structures exhibit nearly linear behaviors as functions of composition, whereas the bandgaps of copolymers with dissimilar parent monomers exhibit nearly monotonic deviations from linearity. On the other hand, the electron and hole effective masses of copolymers with similar parent monomers do not show a significant dependence on composition, whereas for copolymers with dissimilar parent monomers these quantities also display nearly monotonic deviations from linearity. A qualitative rationalization of these trends in terms of the strengths of the inter‐parent–monomer interactions, which bears an intriguing resemblance to the behavior of the vapor pressure of binary solutions, is provided.